2022
DOI: 10.1111/ger.12650
|View full text |Cite
|
Sign up to set email alerts
|

Use of smartphone photos to document the oral care status of nursing home residents

Abstract: Investigate whether clinically assessed oral care status by an external dentist can be replicated using smartphone photographs.Background: Many people with care needs have poor oral hygiene. To help maintain oral health, caregivers require a simple way of communicating oral care status to the dental team. Materials and Methods: Cross-sectional study in which smartphone photographs of the oral and prosthetic care situation of N = 50 nursing-home patients (mean age 85.6 [SD 6] years, 74% women) were assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the field of dental traumatology and oral medicine, studies have concluded that using images captured with smartphones is an effective means of remotely diagnosing traumatic dental injuries and high-risk lesions in the oral cavity [18,19]. Additionally, the use of smartphone photos to document the oral care status of nursing home residents has also been proven beneficial [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of dental traumatology and oral medicine, studies have concluded that using images captured with smartphones is an effective means of remotely diagnosing traumatic dental injuries and high-risk lesions in the oral cavity [18,19]. Additionally, the use of smartphone photos to document the oral care status of nursing home residents has also been proven beneficial [20].…”
Section: Introductionmentioning
confidence: 99%